The fabrication of bilayer polylactic acid films from cross-linked starch as eco-friendly biodegradable materials: Synthesis, characterization, mechanical and physical properties. (15th March 2020) - Gürler, Nedim; Paşa, Salih; Hakkı Alma, M.; Temel, Hamdi
Graphical abstract: Highlights: Biodegradable and eco-friendly materials were synthesized and characterized. Potato wastes recovered from potato chips producing were used for starch source. Cross-linked bilayered films were fabricated with starch and polylactic acid (PLA). Tensile strength, elongation, water vapor permeability, and solubility were examined. Cross-linked bilayered films demonstrated significant mechanical-physical properties. Abstract: In this study, pure potato starch (PPS) was purified from waste potato residual to fabricate cross-linked bilayer materials with the casting method. Malonic acid (MA) was employed to get cross-linked material from PPS as PPS-MA. Then polylactic acid (PLA) was also implemented onto PPS and PPS-MA to produce bilayer materials as PPS-PLA and PPS-MA-PLA. The obtained these bilayer films were characterized by FTIR, XRD, and TGA. The mechanical and physical applications such as water vapor permeability, water uptake, moisture content, solubility, and opacity were investigated. The biodegradation calculations were also done by the process of composting. It has demonstrated that each application onto PPS increased the mechanical features. However, elongation wasn't seen during the breaking test of PPS and PPS-MA films, whereas the PPS-PLA and PPS-MA-PLA films demonstrated 9.34% and 10.14% elongation at break that substantiates the structural durability against rupture, fragmentation, and feeble. Furthermore, the water vapor permeability, water uptake, moisture content, and solubility decreased but the opacity has increased.